The Importance of Clinical Supervision to Improve Teachers' Pedagogical Practices in Elementary Schools - Evi Nurlaila; Anistia Rizki Khoirun Nisa (Journal of Educational Research, Evaluation and Supervision, 2024)
This research is motivated by the importance of clinical supervision to improve the pedagogical practices of teachers in elementary schools. The pedagogical competencies possessed by teachers encompass the domains of knowledge, attitudes, and skills. The pedagogical practices of teachers are related to attitudes and skills in direct interaction with students, which will then have a direct impact on the students. Pedagogical practices for teachers in elementary schools will have a significant impact on the cognitive, affective, and psychomotor aspects of students. Through pedagogical practice, teachers can understand the characteristics of students and identify their potential, interests, and talents. The characteristics of students are also very varied and unique, therefore their potential, interests, and talents are also certainly different. Therefore, it is important to evaluate this through clinical supervision. The research methods used were literature study analysis and descriptive qualitative. Data collection techniques through relevant research literature as well as interviews, documentation, and observation. The results of the research through interviews and literature review indicate that clinical supervision aimed at improving the pedagogical practices of elementary school teachers is important because it plays a very significant role in efforts to achieve learning objectives and the quality of education. This is based on research observations that many teachers still pay little attention to the quality of pedagogical practices because their role as teachers is only considered a teaching routine, clinical supervision has not yet facilitated teachers in addressing pedagogical practice issues due to its classical nature, and there is still a low awareness among elementary school teachers to reflect on pedagogical practices.